Sebuah MITIGASI AKIBAT PENCEMARAN SENJATA KIMIA SARIN UNTUK MENGURANGI BENCANA NUBIKA - Nurfitriani, Wulan; G. Royke Deksino; Jupriyanto , Jupriyanto; M. Taufiq Ramadhan (CV. AFDIFAL MAJU BERKAH, 2024)
The misuse of chemical weapons can have highly dangerous consequences for both humans and the surrounding environment. One of the deadliest chemical weapons is sarin, which can lead to death within minutes of exposure. To reduce the consequences of a chemical weapons disaster, effective contamination mitigation is required. This research employs a qualitative descriptive method, with a literature review study, to discuss contamination mitigation strategies that can be used to minimize the consequences of a chemical weapons disaster caused by the use of sarin. Some of these strategies include the use of protective clothing, gas masks, and environmental decontamination. In emergency situations, protective clothing and gas masks can help shield individuals from exposure to chemical weapons. Furthermore, timely environmental decontamination can aid in reducing contamination levels and the risk of exposure. In addition to contamination mitigation strategies, preventive efforts are also crucial in lessening the impact of a chemical weapons disaster involving sarin. Prevention efforts involve chemical weapon surveillance, training and education, as well as the development of better detection and protection technologies. By implementing the appropriate contamination mitigation strategies and effective prevention efforts, it is hoped that the consequences of a chemical weapons disaster involving sarin can be significantly reduced.